The Development of Accelerated Learning System to Enhance Motivation in Business English Learning for Undergraduate Programs - Thapphet, Saowanee; Prachyapruit, Apipa; Bovornsiri, Varaporn (International Journal of Social Sciences and Management, 2017)
This research aimed to 1) analyse the situations and problems of Business English instruction, 2) examine the accelerated learning system to enhance motivation in Business English learning for undergraduate programmes by means of a focus group of 10 people, and 3) evaluate the accelerated learning system to enhance motivation in Business English learning for undergraduate programmes. The sample consisted of 30 Chairs of Management, the focus group with 10 experts, and the experimentation with 34 students, while the three steps of the research process included 1) the examination of concepts and theories, 2) the learning system development, and 3) the learning system experimentation. The data were analysed using percentages, mean, standard deviation, and t-test (dependent samples), and the paired difference was analysed using LSD and one-way analysis of variance. According to the results of the learning system development, the system consists of the following components: 1) input, 2) process, and 3) output and feedback. Meanwhile, the system process elements include the: 1) principles, 2) objectives and 3) evaluation and assessment of training, contents, training activities, and roles of instructors and learners. The learning system evaluation results reveal that the pre- and post-trial difference of learners’ Business English knowledge to be at the statistical significance level of .05. Also, the pre- and post-trial motivation was different with an increase at the statistical significance level of .05. With respect to the level of satisfaction towards the learning system, the learners’ satisfaction towards the learning system was found to be at the highest level. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 185-191